Nanomechanical Characterization of Cement-Based Materials - Barbhuiya, Salim (IGI Publishers, 2014)
Nanoindentation technique is used to assess the mechanical properties of materials at nano-level. A very small tip (usually diamond) produces indents at the surface of the material to be tested. A load vs. deflection curve is generated and is used to study the elastic properties of materials. Generally, it is used for obtaining the hardness and Young’s modulus of materials at nano-meter scale. Currently, the method to evaluate the mechanical properties by nanoindentation is restricted to homogeneous materials. Cement-based materials are heterogeneous in nature. Therefore, nanoindentation study of cement-based materials is critical and requires several important steps, which need to be performed accurately. This chapter provides a review of the theory of nanoindentation, instruments being used for nanoindentation, sample preparation techniques, indentation strategy, and determination of nanomechanical properties and data analysis for cement-based materials.